ATR prevents Ca2+ overload‐induced necrotic cell death through phosphorylation‐mediated inactivation of PARP1 without DNA damage signaling. Issue 5 (3rd April 2021) - Li, Zhengke; Wang‐Heaton, Hui; Cartwright, Brian M.; Makinwa, Yetunde; Hilton, Benjamin A.; Musich, Phillip R.; Shkriabai, Nikolozi; Kvaratskhelia, Mamuka; Guan, Shengheng; Chen, Qian; Yu, Xiaochun; Zou, Yue
Abstract: Hyperactivation of PARP1 is known to be a major cause of necrotic cell death by depleting NAD + /ATP pools during Ca 2+ overload which is associated with many ischemic diseases. However, little is known about how PARP1 hyperactivity is regulated during calcium overload. In this study we show that ATR kinase, well known for its role in DNA damage responses, suppresses ionomycin, glutamate, or quinolinic acid‐induced necrotic death of cells including SH‐SY5Y neuronal cells. We found that the inhibition of necrosis requires the kinase activity of ATR. Specifically, ATR binds to and phosphorylates PARP1 at Ser179 after the ionophore treatments. This site‐specific phosphorylation inactivates PARP1, inhibiting ionophore‐induced necrosis. Strikingly, all of this occurs in the absence of detectable DNA damage and signaling up to 8 hours after ionophore treatment. Furthermore, little AIF was released from mitochondria/cytoplasm for nuclear import, supporting the necrotic type of cell death in the early period of the treatments. Our results reveal a novel ATR‐mediated anti‐necrotic mechanism in the cellular stress response to calcium influx without DNA damage signaling.